Bioekologi Ikan Sidat (Anguilla sp) dari Perairan Provinsi Bengkulu - Maya Anggraini Fajar Utami; Dewi Purnama; Suprianty JH Sinaga; Dwanda Fachlevy; Tri Gusti Sumarni; Yenni Putri Sari (Universitas Bengkulu, 2025)
Eel (Anguilla spp.) is a food fish with significant economic value and is found in rivers that border the ocean. Studying the relationship between the biological and ecological factors of eel is essential to determine species diversity, fish size, and environmental aspects. This study aims to identify eel catches based on external morphological characteristics and ecological aspects found in Bengkulu Province. The method used in this research is a survey method with eel samples collected through purposive sampling and measurements of water parameters from three rivers: the Jenggalu River, Riak Siabun, and Air Manna. Based on the research results, Anguilla bicolor was found in the Jenggalu and Riak Siabun rivers. In the Manna River, two species of eel were identified: Anguilla marmorata and Anguilla bicolor. Water quality parameter measurements indicatedin the optimal condition for eel growth in all three rivers, which featured sandy mud and rocky gravel substrates Keywords: Biology, Ecology, Eel, Water Quality, River